Концепція безпекового середовища на прикладі стратегій Національної поліції України: ціннісно-економічний та духовний акцент - Кріцак, І. В.; Kritsak, I. V.; Іван Кріцак (Юридичний науковий електронний журнал. - 2022. - № 11. - С. 562-566, 2022)
Розглянуто концептуальні питання нинішнього безпекового середовища України. Актуалізовано роль духовно-ціннісного складника у напрямку вибудовування високого рівня економічної стабільності держави шляхом формування відповідної правової свідомості та правової культури громадян, з концептом (стратегій і тактик) загальнонаціонального рівня. Розглянуто роль Національній поліції України у цих процесах, коли левова частка правоохоронних функцій нашої держави випадає саме на неї. Загалом від якісного (ефективного) виконання поліцейських функцій в аспекті служіння у тісній взаємодії з іншими державними органами та громадськістю залежатиме порядок у державі, що не допустить війни. Узагальнено міжнародний досвід ефективних правоохоронно-оборонних практик у спільній взаємодій в умовах російсько-української війни. Наголошено на міждисциплінарній позиції дослідження питань безпеки країни, що забезпечить стабільність життя і здоров’я людини, її прагнення до пізнання істин. Серед пріоритетних напрямів безпекового середовища виокремлюється наукометрія, кібербезпека, ціннісна складова як запорука стабільності економіки.

The author considers the conceptual issues of the current security environment of Ukraine. The role of the spiritual and value component is updated in the direction of building a high level of economic stability of the state by forming the appropriate legal awareness and legal culture of citizens, with the concept (strategies and tactics) national level. A significant role in these processes belongs to the National Police of Ukraine, when the lion's share of law enforcement functions of our state falls on her. In general, from high-quality (effective) performance of police functions in the aspect of service in close interaction with others state bodies and the public order in the state will depend, which will prevent war. Overcoming negative states security environment of the country by by identifying the real reasons criminogenic conditions (including taking into account the actions of conceptual (invisible) power is the main task of criminology in detection of such negatives. On the other hand, by passing the test on relation to spiritual and cultural values are produced true meanings genetic conditions of a person, laid down millennia of Ukrainian history(this is how the real genetic code of the nation turns out in the pursuit of holiness of life, filling it with spiritual ideals and essence). International experience is summarized effective law enforcement and defense practices in joint interaction in the conditions of the RussianUkrainian war. Interdisciplinary is emphasized the positions of research issues security of the country, which will ensure stability of human life and health, her desire to know the truths. Among the priority directions of the security environment scientometrics is distinguished cyber security, a valuable component of how guarantee of economic stability. Relevant threats and challenges are conceptualized in in conditions of instability of the situation on examples of developed strategies for 2023–2027.

Рассмотрены концептуальные вопросы нынешней среды безопасности Украины. Актуализирована роль духовно-ценностной составляющей в направлении построения высокого уровня экономической стабильности государства путем формирования соответствующего правового сознания и правовой культуры граждан, с концептом (стратегий и тактик) общенационального уровня. Рассмотрена роль Национальной полиции Украины в этих процессах, когда львиная доля правоохранительных функций нашего государства выпадает именно на нее. В целом, от качественного (эффективного) выполнения полицейских функций в аспекте служения в тесном взаимодействии с другими государственными органами и общественностью будет зависеть порядок в государстве, которое не допустит войны. Обобщен международный опыт эффективных правоохранительно-оборонных практик в совместном взаимодействии в условиях российско-украинской войны. Отмечена междисциплинарная позиция исследования вопросов безопасности страны, что обеспечит стабильность жизни и здоровья человека, его стремление к познанию истин. Среди приоритетных направлений среды безопасности выделяется наукометрия, кибербезопасность, ценностная составляющая как залог стабильности экономики.
The concept of a secure environment on the example of strategies National Police of Ukraine: value-economic and spiritual accent
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; безпекове середовище; safe environment; среда безопасности; російсько-українська війна; Russian-Ukrainian war; русско-украинская война; правоохоронні органи; law enforcement agencies; правоохранительные органы; кримінотеологія; криминотеология; національна безпека; national security; национальная безопасность; оборонна практика; defense practice; оборонная практика; наукометричність; scientometricity; Національна поліція України. National police of Ukraine. Национальная полиция Украины; зарубіжний досвід; foreign experience; зарубежный опыт; духовний акцент; spiritual accent; духовный акцент; економічна складова; стратегія